OPTIMASI KOMPOSISI KARBOPOL DAN NATRIUM KARBOKSIMETILSELULOSA SEBAGAI SISTEM BUCCAL MUCOADHESIVE TABLET PROPRANOLOL HIDROKLORIDA - Irawan, Eka Deddy; Munawaro, Siti; Sari, Lusia Oktora Ruma Kumala (Fakultas Kedokteran Gigi Universitas Jember, 2012)
The purpose of this study is to provide controlled release dosage by avoiding first pass metabolism and enzymatic degradation. Propranolol hydrochloride mucoadhesive buccal tablets was prepared by direct compression method using carbopol and CMC Na as buccal mucoadhesive polymer. Buccal mucoadhesive strength measured using buccal mucosa of gout. Testing the release of propranolol hydrochloride was determined by dissolution test using phosphate buffer solution pH 6,8 for 8 hours. Dissolution efficiency (DE) was calculated to describe the overall release profiles and used in determining the optimum response. The optimum region is determined using factorial design with the design criteria of response force for 20-40 grams of mucoadhesive buccal and DE480 between 45-55%. The amount of carbopol that can provide the optimum response is between the range of 53,27-55 mg while the amount of CMC Na can provie the optimum response range is between 70-100 mg.